Ground to Dust: Collisional Cascades and the Fate of Kardashev II Megaswarms - Lacki, Brian C. (The Astrophysical journal, 2025)
Extraterrestrial intelligences are speculated to surround stars with structures to collect their energy or to signal distant observers. If they exist, these most likely are megaswarms, vast constellations of satellites (elements) in orbit around the hosts. Although long-lived megaswarms are extremely powerful technosignatures, they are liable to be subject to collisional cascades once guidance systems start failing. The collisional time is roughly an orbital period divided by the covering fraction of the swarm. Structuring the swarm orbits does not prolong the initial collisional time as long as there is enough randomness to ensure collisions, although it can reduce collision velocities. I further show that once the collisional cascade begins, it can develop extremely rapidly for hypervelocity collisions. Companion stars or planets in the stellar system induce perturbations through the Lidov–Kozai effect among others, which can result in orbits crossing within some millions of years. Radiative perturbations, including the Yarkovsky effect, also can destabilize swarms. Most megaswarms are thus likely to be short-lived on cosmic timescales without active upkeep. I discuss possible mitigation strategies and implications for megastructure searches.